FRI0221 Occurrence of Serious Infection in Patients with Rheumatoid Arthritis Treated with Biologics and Denosumab Observed in A Clinical Setting. (15th July 2016) - Wong-Pack, M.; Rodjanapiches, R.; Lau, A.; Ioannidis, G.; Wade, S.; Balasubramanian, A.; Lin, C.J.; Roy-Gayos, P.; Bensen, W.G.; Bensen, R.; Adachi, J.D.
Abstract : Background: Studies combining immunosuppressive biologics have shown an increased risk of infections. Objectives: Examine the occurrence of serious and opportunistic infections in RA patients treated concurrently with DMAb and an immunosuppressive biologic, and those treated with only an immunosuppressive biologic. Methods: We reviewed RA patients from two rheumatology practices in Ontario (Canada) between 01July2010 and 31July2014. Eligible patients were ≥18 years of age with RA, registered in the practice ≥3 months before and after the index date, and received ≥1 injection/infusion or filled a prescription for an immunosuppressive biologic therapy for RA. Patients with HIV or AIDS, or who were receiving cancer treatment or immunosuppressive therapies for conditions other than RA or living in a nursing home were excluded. The incidence of serious infections was counted for two different groups: 1) those who had used DMAb and an immunosuppressive biologic concurrently and 2) those who had used an immunosuppressive biologic alone. Serious infection was defined as resulting in hospitalization or an emergency room (ER) visit with associated use of IV antibiotics and a primary diagnosis of infection. The observational period was from the index date to 31July2014 or loss to follow-up, whichever came first. For the concurrent group, index date was defined as their first DMAb injection. A frequency-matching technique utilizing the index date of the concurrent group was used to select the index date of the biologic-alone group. Results: 308 patients met the eligibility criteria; patient characteristics (± 6 months of index event) are shown below. Three events of serious infection occurred in three patients in the concurrent group (all three were cases of pneumonia); four events of serious infection occurred in four patients in the biologic-alone group (three cases of pneumonia, one upper respiratory tract infection, all resulting in hospitalization). One event of opportunistic infection ( mycobacterium avium complex and pleural infection) occurred in the biologic-alone group. All patients recovered, with no instances of death. Conclusions: RA patients may require treatment for bone loss due to intrinsic disease, steroid use, and advancing age. This study demonstrates a low occurrence of serious infections in biologically-treated RA patients, including patients with concurrent DMAb use. Acknowledgement: Study funded by Amgen Inc; Claire Desborough, an Amgen employee, provided writing assistance. Disclosure of Interest: M. Wong-Pack: None declared, R. Rodjanapiches: None declared, A. Lau Consultant for: Amgen, Abbvie, Celgene, Roche, UCB, Speakers bureau: Amgen, Abbvie, G. Ioannidis: None declared, S. Wade Consultant for: Amgen, A. Balasubramanian Shareholder of: Amgen, Employee of: Amgen, C. Lin Shareholder of: Amgen, Employee of: Amgen, P. Roy-Gayos: None declared, W. Bensen Grant/research support from: Amgen, Abbvie, Roche, Janssen, Consultant for: Eli Lilly, Amgen, UCB, Abbvie, BMS, Janssen, Pfizer, Roche, AstraZeneca, R. Bensen: None declared, J. Adachi Grant/research support from: Amgen, Eli Lilly, Marck, Consultant for: Activas, Amgen, Eli Lilly, Merck, Speakers bureau: Amgen, Eli Lilly, Merck